The rise of an Alaskan Native bourgeoisie - Mason, Arthur (Études/Inuit/Studies, 2002)
AbstractThis article tells the story of a group of Alaska indigenous leaders’ transition to capitalism. With Congressional passage of the Alaska Native Claims Settlement Act (ANCSA) in 1971, a new economic position emerges in Alaska Native society which creates opportunities for indigenous leaders to develop an awareness of themselves as a particular type of entrepreneurial group. Based on observation and analysis, this story traces the development of Kodiak Island Native leaders and relates their enduring apprehension as emerging capitalist agents who become conscious of their role as bearers of a project of identity formation. I claim that pre-ANCSA Kodiak society is a particular system of stratification in which social and cultural sources of power and privilege are dominant. The transition to post-ANCSA society is a process of converting devalued forms of power into new, economically defined forms and marks a shift from rank order to capitalist class stratification.